Treatment outcome and identification of factors influencing overall survival after Lu-177-PSMA-617 radioligand therapy in metastatic prostate cancer - Schneider, Charlotte A.; Täger, Philipp; Hammes, Jochen; Fischer, Thomas; Drzezga, Alexander; Pfister, David; Heidenreich, Axel; Schmidt, Matthias (Nuklearmedizin - NuclearMedicine, 2021)
Objective To examine the clinical benefit of Lu-177-PSMA-617 radioligand therapy for patients with metastatic castration-resistant prostate cancer (mCRPC).Patients and Methods Between November 2014 and December 2018, a total of 56 consecutive patients (median age 69.5 years; range 55–84 years) with mCRPC were included in this retrospective analysis. Patients received between 1 and 4 therapy cycles with a mean activity of 6.8 GBq per cycle. Biochemical response was evaluated using Prostate Cancer Working Group Criteria 3 (PCWG 3). Survival was assessed using Kaplan-Meier estimates and Cox proportional hazards regression analysis. This retrospective study was approved by the local ethics committee.Results A total of 139 treatment cycles with Lu-177-PSMA-617 were performed. A decline of 50% or more of prostate-specific antigen (PSA) level occurred in 54% and a PSA decline of any amount in 65% of patients. The estimated median overall survival (OS) was 16 months, in the chemotherapy subgroup 14 months. A longer OS was associated with a PSA-decline ≥50%, more than 2 cycles of therapy, cumulative activity >15 GBq and an initial alkaline phosphatase ≤ 220 [U/l]. These identified predictors remained significant on uni- and multivariate Cox regression analysis. Moreover, 40% of the patients who were non-responders after the first therapy cycle turned into responders after the second one.Conclusion PSA-decline ≥50%, a cumulative activity >15 GBq and an initial alkaline phosphatase ≤ 220 [U/l] were identified as key predictors of prolonged OS in patients with mCRPC. In contrast rapid clinical deterioration mostly due to skeletal carcinomatosis resulted in early treatment failure.
Keywords: Prostatakarzinom; Lu-177-PSMA-617; Radioligandentherapie